Mobile-App-based Authentication Framework for cloud computing - Ankush Kudale, Dr. S. Hemalatha (International Journal of Advanced Science and Technology, 2020)
Cloud computing has been growing day by day. It has been spreading almost all areas of market. Cloud computing has various merits beneficial to the cloud user, but it has some demerits also, where authentication is very important security issue. To access cloud computing server or its services users need to login on web. User authentication and access control process need to be scrutinized properly. Various methods of authentication are available in the market today, but there are loopholes that stand in the way of guaranteeing complete security and hence many organizations hesitate to seek cloud services. The mobile tokens (soft token) are the future of the authentication industry. Most modern users keep using smart phones with dozens of apps with convenience with similar methods of authentication.  In this paper, we have proposed a new mobile-app-based authentication framework for cloud computing users using app without internet too. The proposed framework provides a feasible and efficient mechanism to integrate existing systems. The framework provides protection from unauthorized access, easier to use for the employee and to deploy for the administrator. So, it will be higher cloud security with more convenience. The framework will be incorporated in the upcoming cloud computing services.